Bangkok’s Bunnag Lineage from Feudalism to Constitutionalism: Unraveling a Genealogical Gordian Knot - Van Roy, Edward (The Journal of the Siam Society, 2020)
Long before the royal edict of 1913 prescribing Thai surnames, generations of Bunnag notables, not yet carrying that cognomen, played a commanding role in Thai political, economic, and social affairs. From the start of the Bangkok era in 1782 to the end of the absolute monarchy in 1932 the Bunnag nobility passed through more than five generations, rising to unprecedented prominence and then waning under an upsurge of royal power followed by constitutional leveling. This article reviews that generational sequence through a résumé of the Bunnag family’s complex genealogy, a veritable Gordian Knot of family ties set in a fast-changing society. In the interests of simplicity, it focuses on the most eminent family members, their careers and filial, fraternal, and factional relations, accompanied by passing reference to the history of their Khlong San stronghold, as an approach to deciphering the place of the Bunnag lineage in Thai political and social affairs over the course of the Bangkok era. In the process, an opportunity is afforded to review some of the institutional foundations of Thai elite culture under the ancien régime and probe, from the Bunnag perspective, some of the political dynamics associated with the kingdom’s ongoing transformation from feudalism to monarchial absolutism to constitutionalism.